Implementasi Algoritma Skipjack Dalam Pengamanan File Video - Gaol, Rina Wanty Lumban (TIN: Terapan Informatika Nusantara, 2021)
The problem that lies within the scope of the video is where the privacy video can be watched by unauthorized people if the video file is unsecured. In the event of a burglary and theft of important data information in a video file, it will be detrimental to interested parties. Therefore, we need an application system to be able to secure the video file. To minimize this, a second level of security is needed by scrambling the video so that the visual information from the video cannot be seen by people who do not have a key. Then the information in the video file is changed in the form of codes or signals where this code will be manipulated. Thus the authors feel the video files need to be secured with good security. So it is necessary to make encryption and decryption on video files. The skipjack algorithm is one of the cryptographic algorithms that can be used to secure video files. The skipjack algorithm is a 64-bit codebook electronic algorithm that changes a 64-bit input block to a 64-bit output block. The parameters used for encryption are 80-bit keys, and have 32 rounds for the encryption and description process. This study describes how to secure video files based on the skipjack algorithm.